Synthesis and crystal structure of 3-methyl-2-(methylthio)-4H-chromen-4-one, C12H12O2S - Liu Feng; Zhang Yuming; Zhao Zhimeng; Liu Yi; Chen Yang; Xiao Tao (Zeitschrift für Kristallographie - New Crystal Structures)
C12H12O2S, monoclinic, P21/c (no. 14), a = 7.4771(1) Å, b = 8.6860(1) Å, c = 16.0445(2) Å, β = 95.374(1)∘ $95.374{\left(1\right)}^{° }$ , V = 1037.45(2) Å3, Z = 4, R gt(F) = 0.0311, wR ref (F 2) = 0.1156, T = 293(2) K.